The Relationship Between Eyebrow Elevation and Height of the Palpebral Fissure: Should Postoperative Brow Descent be Taken into Consideration When Determining the Amount of Blepharoptosis Correction? - Edward Ilho Lee; Nam Ho Kim; Ro Hyuk Park; Jong Beum Park; Tae Joo Ahn (Archives of Aesthetic Plastic Surgery, 2014)
Background Combining blepharoptosis correction with double eyelid blepharoplasty is common in East Asian countries where larger eyes are viewed as attractive. This trend has made understanding the relationship between brow position and height of the palpebral fissure all the more important in understanding post-operative results. In this study, authors attempt to quantify this relationship in order to assess whether the expected postoperative brow descent should be taken into consideration when determining the amount of ptosis to correct. Methods Photographs of ten healthy female study participants were taken with brow at rest, with light elevation and with forceful elevation. These photographs were then viewed at 2 x magnification on a computer monitor and caliper was used to measure the amount of pull on the eyebrow in relation to the actual increase in vertical fissure of the eye. Results There was a positive, linear correlation between amount of eyebrow elevation and height of the palpebral fissure, which was statistically significant. Brow elevation increased vertical fissure, and thereby aperture of the eye, by 18%. Conclusions Although the eye-opening strength as well as height of the palpebral fissure is improved with ptosis repair, the true effectiveness of ptosis surgery is diminished by the associated descent of the brow from relief of the involuntary frontalis muscle action and this should be taken into account prior to surgical intervention. Regardless, the combination of frontalis muscle relaxation and the increased eye-opening strength from ptosis repair gives the eye and the periorbital region a more natural look.